Impact of direct marketing on consumer buying behaviour: a study on pizza hut, sri lanka - Pushpanathan, A.; Munthazir, M.M.; Kobichanthar, C. (Wayamba University of Sri Lanka., 2018)
Fast food industry has been a lucrative business with higher potential for growth, it is significant to identify consumer requirements and update consumers about new products, promotions to attract consumers. Product information is a vital in creating demand in consumer mind for purchase. There are extensive range of fast food brands available in Sri Lanka. Pizza Hut is leading the fast food industry in Sri Lanka by offering value addition than competitors. The business environment contemporary organizations are operating in is dynamic and complex. Therefore, organizations have to differentiate them from other rivals. Direct marketing is a powerful marketing tool in differentiating organizations by influencing on the purchase intention of consumers. The objective of present study is to explore the impact of direct marketing on consumer buying behaviour of the Pizza Hut. Further the study is identifying the effect of direct marketing methods in selecting suitable strategies and developing marketing mix for Pizza Hut. The study considers consumers’ buying behaviour as the dependent variable and direct marketing modes, consumer purchase intention and brand loyalty as the independent variables. 210 consumers were selected as sample of this study from the Union Place Pizza Hut in Colombo. Structured questionnaires issued amongst the consumers of Pizza Hut for collecting data. The collected data were analysed using correlation and regression analysis in SPSS version 20. Findings of the present study indicated that consumers purchase intention change based on the level of information they received via various direct marketing channels such as direct mail have a stronger influence over their purchase intention. The study recommended that an effective direct mail campaign with identifying appropriate target audiences and also the direct mails will improve consumer conversion for Pizza Hut. Further adding promotion discounts, coupon codes on direct mails will ensure higher consumer attraction towards Pizza Hut.
Keywords: Consumer buying behaviour.; Direct marketing.; Purchase intention.